Appraisal of Energy Transition: International Maritime Organisation’s Forecast in Shipping Industry - OLUSEGUN, O. A.; DANIEL, B. O. (FUPRE Journal of Scientific and Industrial Research, 2024)
This paper examined the proposed transition of energy from the use of fossil fuel to alternative energies in the maritime industry. This is with a view to appraise all options of alternative energies available with their impacts on climate, environment and cost effectiveness. Master Mariners and Chief engineers in Nigeria with their association comprising about 103 in population were reduced to 44 in sample using Yamane formula and designed questionnaire distributed through random sampling techniques. The responses were retrieved via the google form. The result from the analysis showed different levels of strength, weaknesses, opportunity and weaknesses with hybrid and electric being the least to impact climate but somehow costly in the areas where the electricity is unstable, while biogas is available and cheap production is difficult and may affect agriculture, landuse, e.t.c. All other kinds of fuel were explained according to their SWOT explanations. Attempt should be made to increase the use of electric energy and hybrid from ships though it will be limited in power, biogas and other renewable energies can be worked on to have a better environment and good climate with cost effectiveness in the long run. Considering all the aforementioned issues, it is imperative for IMO to consider this SWOT analysis and observe all areas of interest with a view to formulate polices and encourage sustainable ship building and fuel that is to be used to achieve the vision of 2050.
This paper examined the proposed transition of energy from the use of fossil fuel to alternative energies in the maritime industry. This is with a view to appraise all options of alternative energies available with their impacts on climate, environment and cost effectiveness.
Keywords: Fossil Fuel; Alternative Energies; Maritime Industry Master Mariners; Chief Engineers